PENDEKATAN EXPERIENCE ECONOMY PADA PEMASARAN FESTIVAL PARIWISATA: PENGARUH TERHADAP KEPRIBADIAN FESTIVAL YANG DIRASAKAN PEGUNJUNG DAN REPUTASI FESTIVAL - Ares Albirru Amsal; Harryadin Mahardika (Universitas Mercu Buana, 2017)
Abstract: Tourism is one of the most essential sector for several countries because itaffects the economic growth. Festival, as a part of event tourism, can be used as touristattraction. To achieve success in festival, some conditions have to be fulfilled i.ememorable experience of festival, keen festival personality and its reputation. Pine andGilmore (1998) described four dementionals of experience economy which are;education, entertainment, escapism and esthetic. Using Structural Equation Modeling(SEM) on Festival Makanan Kampoeng Tempo Doeloe (206 samples), this studyconducted to determine the effect of four experience dementions on festivalpersonality and the influence of festival personality towards reputation. The result areshowed that entertainment, education and esthetic have the significant positive effecton the festival personality. This study also reveals that festival personality have asignificant positive influence on reputation. This research can be useful forgovernment or tourism event organiser while organising festivals.